The shifting biogeography of reef corals during the Oxfordian (Late Jurassic). A climatic control? - Martin-Garin, Bertrand; Lathuilière, Bernard; Geister, Jörn (Palaeogeography, palaeoclimatology, palaeoecology, 2012)
Until recently, the Jurassic was thought to have been a period characterised by a predominantly warm and equable climate. During the Oxfordian (a time span of six million years in the Late Jurassic) the distribution of tropical coral reefs was limited to about 35°N and near to 25°S. However, in Middle Oxfordian time, coral reefs were abundant only at higher latitudes and almost entirely missing near the equator. During that time the area of maximum reef development had shifted poleward to a belt lying between 20°N and 35°N, leaving hardly any coral formations at the lower inner-tropical latitudes. After demise towards the end of Middle Oxfordian time, the low-latitude reefs recovered during the Late Oxfordian, accompanied by a southward migration of reef corals in the northern hemisphere. As suggested by stable isotope and palynological data, the faunal migration can be correlated with a significant rise in seawater temperature during the Middle Oxfordian. ► A great reef coral and coral reef database compiled from literature and fieldwork ► First time focus on a single geological stage for reef corals, Oxfordian–Jurassic ► Distribution and generic diversity of Oxfordian scleractinian corals ► Distribution, growth, evolution and limiting factors which control the coral reefs ► A climatic scenario suggested for the fate of Oxfordian coral reefs